Flexible skin-contact antenna with artifical magnetic conductor for health monitoring application - Othman, Nazirah (2022)
Flexible antenna plays a significant role to ensure efficient wireless communication in wearable devices. The choice of the dielectric substrate material of the antenna is one of the important factors to ensure good antenna performance while being tolerant to mechanical deformation. In addition, the size of the antenna becomes the main issue in designing the antenna for on-body applications. Furthermore, the radiation and transmissions performance of the on-body antenna suffers from performance degradation due to several factors such as dielectric properties of the human body as well as line of sight (LOS) and non line of sight (NLOS) transmission conditions. Therefore, this study presents a flexible Skin-Contact Antenna with Artificial Magnetic Conductor surface (SCA-AMC) made from medical-friendly material. Initially, three different types of medical materials which include transdermal cotton patch, semi-transparent film, and self-adhesive bandage were proposed for investigation as the antenna’s dielectric substrate. The dielectric properties of the proposed materials were measured prior to the antenna design. For preliminary design investigation, a conventional bowtie antenna was designed using the proposed medical materials and optimized to operate at frequency of 2.4 GHz. To achieve the objectives, the feasibility of medical material usage for the antenna’s substrate was explored based on wetness and repeatability test. The proposed SCA is intended for on-body wireless communication devices where there is a significant limitation on the overall size of the antenna. In order to develop a compact flexible antenna, a meandering technique is applied to the conventional bowtie antenna. By employing the meandering technique, the total length of the antenna can be reduced by 20 %. As the body protection against electromagnetic absorption is important, a dipole-like AMC structure was designed at frequency of 2.4 GHz and integrated with the meandered bowtie antenna. The proposed SCA-AMC is made of flexible material for the substrate and conducting parts, making it suitable for wearable applications. Furthermore, the factors that influence the antenna’s radiation and transmission performance have been determined. The experiments have been carried out considering various conditions such as body movements and the presence of either human body or obstacle in between the SCAAMC transmitter and the receiver. The results indicate that the human body introduces an additional 20 dBm power loss when present between the transmitter and receiver. Also, the presence o f the book causes 6 dBm reduction in received power while sweatshirts and cotton polo shirts contribute to a small variation of approximately from 0.5 to 1 dBm. Besides, wetness measurements were also carried out using tap water and sweat-like solution. The sweat-like solution had been developed using a mixture of sodium chloride, sodium bicarbonate, and water. The material characterization of the developed sweat-like solution was then performed. The developed sweat-like solution has a measured permittivity and loss tangent of 75.8 and 0.13, respectively at the frequency of 2.4 GHz. The proposed SCA-AMC was also tested in a real-life situation by merging it with an electrocardiogram (ECG) sensor node. The results obtained show that the wireless ECG pattern is comparable to the ECG pattern measured using a conventional ECG machine. The findings in this research have profound implications for future studies to develop an efficient wireless device, especially for on-body applications.